COVID-19 PANDEMIC: ITS IMPACT ON THE EXISTENCE OF BUSINESS ACTORS IN TRADITIONAL MARKETS - Syamsul Syamsul; Siti Masyita (Berkala Akuntansi dan Keuangan Indonesia, 2021)
Currently, the World is hit by the COVID-19 pandemic. The impact of this pandemic, is not only life threatening, but also has an economic downturn that is evenly distributed in almost all countries, including Indonesia. This study aims to determine and analyze the impact of the COVID-19 pandemic on the existence of business actors in traditional markets. The polls and samples of this study were chicken and egg traders at Manonda Central Market, Palu. Primary data was obtained through distributing questionnaires to research respondents. Based on the results of descriptive analysis and test one-way anova, it was found that there were differences in profit, sales turnover, and the number of buyers before and during the COVID-19 pandemic. This means that the COVID-19 pandemic threatens the existence of business actors in traditional markets. This research is useful for policy makers in maintaining the existence of business actors during the current COVID-19 pandemic